Hollowing out probation?: the roots of Transforming Rehabilitation - Deering, John (Probation journal, 2019)
This article provides a critical perspective on the political and policy history of probation in England and Wales to develop a better understanding of how TR came to be. TR was only the latest act in a longstanding process of changing probation to fit ideological ‘flavours’, and we suggest that it is the hidden nature of probation work in combination with a lack of public legitimation work by probation institutions and probation staff that has placed probation in such a vulnerable position.